2018
DOI: 10.1016/j.indcrop.2018.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Active polylactic acid film incorporated with green tea extract: Development, characterization and effectiveness

Abstract: A new antioxidant active packaging film has been developed based on polylactic acid (PLA) in which green tea extract (GTE) has been immobilized by extrusion. Two GTE concentrations were tested, 1% (w/w) and 2% (w/ w). Four GT samples were compared regarding their antioxidant capacity (by DPPH radical scavenging method and β-carotene bleaching method), total phenolics content (TPC) and total flavonoids content (TFC). The commercial GTE presented with highest antioxidant capacity by the DPPH radical assay (EC 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 56 publications
3
49
1
Order By: Relevance
“…In brown algae ( Bifucaria bifurcata and Fucus spiralis ) for example, the total phenolic content varied between 1 mg EAG/g and 29.8 mg EAG/g, depending on the extraction solvent [ 24 ]. It is also interesting to compare cyanobacterial results with green tea, which is considered a powerful natural antioxidant, due to its high content of gallic acid, among other compounds [ 25 ]. A study on the applicability of green tea in antioxidant-active food packaging showed a variation of total phenolic content between 272 mg EAG/g and 416 mg EAG/g, in several green tea samples [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brown algae ( Bifucaria bifurcata and Fucus spiralis ) for example, the total phenolic content varied between 1 mg EAG/g and 29.8 mg EAG/g, depending on the extraction solvent [ 24 ]. It is also interesting to compare cyanobacterial results with green tea, which is considered a powerful natural antioxidant, due to its high content of gallic acid, among other compounds [ 25 ]. A study on the applicability of green tea in antioxidant-active food packaging showed a variation of total phenolic content between 272 mg EAG/g and 416 mg EAG/g, in several green tea samples [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, these studies point to an interest in exploring the antioxidant activity of cyanobacteria, considering their richness of compounds such as carotenoids and polyphenols. Inclusively, some of these authors reported antioxidant activity [ 5 , 13 , 16 , 17 , 19 , 20 ] and/or antioxidant contents [ 11 , 14 , 15 , 21 ] in cyanobacteria quite comparable, and sometimes higher, than those found in eukaryotic microalgae, macroalgae or higher plants [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two aromatic plant extracts have been applied, as a preservative agent or incorporated in food packaging, to different food matrices aiming to extend its shelf-life. These matrices include seafood [15], sardines [16], chicken nuggets [17], Pacific white shrimp [18], hake fillets [19], and smoked salmon [20].…”
Section: Introductionmentioning
confidence: 99%
“…The release kinetics of polyphenol-PLA/PLGA nanoparticles in vitro show rapid release are at first followed by slow release, which demonstrates the controlled release of polyphenol compounds from PLA/PLGA nanoparticles [ 214 ]. Similar to other nanoparticles, PLA/PLGA also enhances the functional activity of polyphenols, such as anti-inflammatory, antioxidant and anti-cancer properties [ 215 , 216 , 217 ].…”
Section: Nanoformulations For Loading and Delivery Of Polyphenolsmentioning
confidence: 99%